Czy warto mieć patrona, czyli co Marian Rejewski zawdzięcza Pedagogicznej Bibliotece Wojewódzkiej im. Mariana Rejewskiego w Bydgoszczy? .......... 143 - Handzel, Agnieszka F. (Skąd się biorą czytelnicy?, 2025)
IS IT ANY GOOD TO HAVE A NAMESAKE, OR HOW IS MARIAN REJEWSKI INDEBTED TO THE MARIAN REJEWSKI PROVINCIAL PEDAGOGICAL LIBRARY IN BYDGOSZCZ?The article discusses the activities of the Marian Rejewski Provincial Pedagogical Library in Bydgoszcz connected with promoting its namesake and his achievements. In the context of the increasing role of personal branding, it is shown how properly tailored activities may contribute to building a strong and identifiable brand of an institution in its local environment. The author presents various initiatives, such as an exhibition, workshops, classes, and an escape room, which give opportunities to promote the person of the namesake.